IDENTITY OF KĀRLIS RŪDOLFS KREICBERGS IN HIS LIFE - Medveckis, Arturs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The aim of the paper is to analyse the identity of Latvian pedagogue and conductor Kārlis Rūdolfs Kreicbergs (1921-2014), by using the author's elaborated theoretical model of identity research (2016), and the integrated author's approbated personality research model (2013). The personality research model, which, in its micro context, includes basic features of his personality - emotions, talent, behaviour and convictions, as well as adaptation characteristics - interests, motivations, values, attitudes, is supplemented with components determining the identity of the pedagogue: in mezzo context in the social environment, where the identity of the pedagogue, as well as family, identity in his everyday life, student's and religious identity is formed, but in micro context, - professional, national, local, political and cultural identity of the personality, thus creating a research model of the multidimensional identity of the teacher and factors influencing development thereof. After the approbated model with the help of qualitative research methods the obtained data are related to theoretical opinions about the identity formation of the pedagogue, thus approving the innovative character of the proposed theoretical model.